The periphery as the center for biodiversity conservation: A case study from the Philippines - Medina, Charito P. (Animo Repository, 2004)
This case study of the MASIPAG model of farmer-managed, on-farm variety trials in the Philippines shows that resource-poor farmers can play a central role in in-situ biodiversity conservation provided there are tangible benefits. The success of the farmers in biodiversity conservation in this case study was strengthened by technical support from non-governmental organizations and scientists. The farmers were active participants in technology development, not passive recipients of technology.